Enzim Papain: Aspek Green Chemistry pada Reaksi Knoevenagel - Haryanto, Laurentius; Cahyana, Antonius Herry (Pharmaceutical Sciences and Research, 2015)
Green chemistry aspect is the chemical approach that has been studied in the past two decade. One of the principles is the development of green synthesis process that is friendly for the environment. This research showed that papain can be used as catalyst for Knoevenagel reaction with 3 kinds of substituted-benzaldehyde and malononitrile as substrates in aqueous medium. The best reaction condition with 80% yield was reached by utilizing of 25 mg papain/mmol substrate. Reaction was conducted at ambient temperature and pressure for 30 min. Products were as yellowish to yellow needle crystals and successfully characterized by melting point, UV-Vis, IR, mass spectra, and 13C & 1H-NMR, named as 2-(4-hydroxybenzylidene)-malononitrile); 2-(3-hydroxybenzylidene)-malononitrile); and 2-(4-hydroxy-3-methoxybenzylidene)-malononitrile).